The impact of digital technologies, recreation, and nutrition on stress management and mental well-being in athletes (2025)
Stress is a natural human experience that depending on its severity and duration, it can have both positive (eustress) and negative (distress) effects. Chronic and unmanaged stress has a negative impact on social mental and physical health whereas moderate stress may improve motivation and adaptability. A comprehensive strategy combining biological, psychological and social techniques is needed for effective stress management. While social support, resilience and psychological relief are all facilitated by recreational activities, stress responses, cognitive function, and emotional equilibrium are significantly influenced by nutrition. Digital interventions have also become widely available and scalable tools for stress management, prevention and monitoring. An integrative review of major database and other sources were conducted. The study included recent empirical, systematic, scoping, narrative reviews and other high-quality articles that is directly related to digital technologies, recreation, nutrition and mental health outcomes in athletes. A total of 46 studies met the inclusion criteria. The review revealed that impact may be positive or negative depending on certain factors. Stress detection, monitoring, recovery management and resilience are enhanced through digital technologies. Recreational activities also improve resilience, regulates emotions, reduce anxiety, stress and depression. Adequate nutrition lowers stress, anxiety, depression and enhance better mental well-being in athletes with nutrition knowledge and positive dietary attitudes enhancing mental resilience. This paper delves into the combined impact of digital technologies, recreation, and nutrition on stress management and mental wellbeing in athletes with impact ranging from mental resilience to self-regulation, autonomy and motivation and social connections. Furthermore, the use of nutrition, recreation with digital technologies fosters cognitive and emotional regulation as well as personalisation and preventive wellbeing system. This study was also able to establish that the combination of digital strategies, recreational and health produce an impact in Athletes well being. When taken as a whole, these tactics highlight how crucial a comprehensive framework is for improving mental health and stress management, especially for athletes and other high-risk groups.